Stress response behavior in different wheat species in relation to heat tolerance - , Kavita; Munjal, Renu; Kumar, Naveen; Dhanda, Satyavir Singh (Journal of Cereal Research, 2016)
Eighty wheat genotypes, twenty each from Triticum aestivum, Triticum durum,Triticum dicoccum and Synthetic T. aestivum were evaluated for terminalheat tolerance by normal (non-stress) and late (stress) planting in field inrandomized block design with three replications for two crop seasons; 2012-13and 2013-14. The genotypes differed significantly for grain yield in non-stressand stress conditions. The heat susceptibility and tolerance indices werecalculated as Heat Sensitivity Index (HSI) and Heat Response Index (HRI)for grain yield. Genotypes PBW 550, HD 2733, HD 2967, PBW 343 & PBW373 from T. aestivum, WHD 943, WHD 945, WHD 314, WHD 946 & WHD912 from T. durum, DI 26, DI 119, DI 88, DI 52 & DI 61 from T. dicoccum andSyn 22, Syn 24, Syn 30, Syn 36, Syn 62 & Syn 25 from Synthetic T. aestivumwere found heat tolerant on the basis of heat susceptibility index and couldbe useful as genetic stock to develop wheat heat tolerant varieties in breedingprograms. Synthetic T. aestivum was found to have lowest HRI followed byT. durum, T. dicoccum and T. aestivum respectively while HSI was lowest inT. durum, T. aestivum, T. dicoccum and Synthetic wheat lines respectively.